Parental Choice Criteria in Preschool Selection: A Qualitative Research in Klang Valley Malaysia - Wong, Sook Yee (2010)
Preschool education and other related services are high in demand within the community of Malaysia. As such, the early childhood education (ECE) sector has become an extremely competitive market, with each of the providers aiming (and claiming) to provide the highest quality of services. However, little is known about parental choice criteria of preschool selection in Malaysia. The aim of this paper is to explore parental choice criteria in preschool selection based on marketing mix elements, and to identify effective marketing strategies for ECE businesses in Klang Valley Malaysia. A set of semi-structured questionnaire was developed to which a total of 17 respondents from Klang Valley participated. All respondents are parents of preschool aged children, data collected through in-depth interview sessions. Qualitative data was studied using content analysis, where phrases were coded and classified into respective categories. Result of this exploratory study showed that marketing mix elements are not the only surfaced criteria for parental preferences in preschool enrolment of their children. It was revealed that other aspects such as affective responses, good relationships, value-added services, fellow students, and transparency of preschool have their roles to play in the criteria of preschool selection. Demographic status, or financial capability, was found to have an impact on parental choice criteria. In sum, the results of this study imply that even though marketing mix elements are not the only list of criteria in parental preference of a preschool, they serve as the base in such consumption behaviour. It was also concluded that the Wheels of Consumer Analysis model compliments with the eight listed marketing mix strategies in the study of consumers’ purchasing behaviour as a whole. Preschools or other related businesses in Malaysia may find this paper useful as a guidance or reference in efforts toward establishing the ‘best’ preschool catered for different target markets. This paper qualitatively sought for interview data to identify the best marketing strategies on ECE businesses performance.